Interhemispheric Differences in Dentifrication and Related Processes Affecting Polar Ozone - Santee, M. L.; Read, W. G.; Waters, J. W.; Froidevaux, L.; Manney, G. L.; Flower, D. A.; Jarnot, R. F.; Harwood, R. S.; Peckham, G. E. (2004)
The severe depletion of stratospheric ozone over Antarctica in late winter and early spring is caused by enhanced CLO abundances arising from heterogeneous reactions on polar stratospheric clouds (PSCs). CLO abundances comparable to those over Antarctica have also been observed throughout the Arctic Vortex, but the accompanying loss of Arctic ozone has been much less severe.